54.6k views
1 vote
AgF (aq) + KNO3 (aq) →

1 Answer

4 votes

Answer:

AgF (aq) + KNO₃ (aq) → AgNO₃(aq) + KF(aq)

Step-by-step explanation:

AgF (aq) + KNO₃ (aq) →

The products from the equation above can be obtained as follow:

1. AgF and KNO₃ will dissociate in solution as shown below:

AgF (aq) —> Ag⁺(aq) + F¯(aq)

KNO₃ (aq) → K⁺(aq) + NO₃¯(aq)

2. A double displacement reaction will occur between AgF and KNO₃ as illustrated below:

AgF (aq) + KNO₃ (aq) →

Ag⁺(aq) + F¯(aq) + K⁺(aq) + NO₃¯(aq) → Ag⁺NO₃¯(aq) + K⁺F¯(aq)

AgF (aq) + KNO₃ (aq) → AgNO₃(aq) + KF(aq)

A careful observation of the above equation shows that the equation is balanced.

User JAQuent
by
6.0k points